Pelaksanaan Penerapan Sistem Kurikulum Merdeka Belajar Mendikbud di SMP Negeri 13 Makassar - Ainun, A Sry; Hasni, Hasni (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2026)
This Study aims to determine: 1). The form of implementing teacher training regarding the concept of Free Learning for the Minister of Education and Culture at SMP Negeri 13 Makassar. 2). Knowing the factors that become obstacles and supports in implementing the Merdeka Learning Mendikbud learning at SMP Negeri 13 Makassar. 3). Knowing the advantages of the Free Learning Ministry of Education and Culture curriculum at SMP Negeri 13 Makassar. The type of research used is descriptive qualitative. The data collection techniques used are interviews and observations. The data collection process carried out by researchers included: preparing data, reflecting on data, coding data, sharing coding results, interpreting, and interpreting data. The research results show 1). The form of implementing the independent learning curriculum carried out by teachers at SMP Negeri 13 Makassar, namely: at the beginning of learning a diagnostic test is carried out, centered on students, planning the learning process according to the needs of students, according to the characteristics/learning styles of students, the learning process is differentiated , and reflection at the end of learning. 2). Factors that become obstacles and supports during the implementation of the independent learning curriculum system at SMP Negeri 13 Makassar, namely inhibiting factors: differences in student characteristics (Human Resources), time mapping, student mindset, and injustice in giving ways to do assignments , while the supporting factors are: with training and guidance, school facilities and infrastructure are fulfilled, using the time provided as well as possible, and understanding the conditions that every human being has differences in capturing a lesson. 3). The advantages of the independent learning curriculum are: more independent, simpler, more liberating in determining the form of learning style/way according to students' abilities, and more relevant.ugj@unm.ac.id.